Study of factors associated with COVID-19 mortality in a rural tertiary health care center - Josna Ganesh Teli; Satish Reddy; Vasantha Kamath; M J Jacob; Dharani Mohan; Kushal Markanday (Wolters Kluwer Medknow Publications, 2021)
Background: COVID-19 has swiftly spread to emerge as a global pandemic with no visible signs of decline. It is imperative to identify the parameters contributing toward COVID-19 mortality to facilitate prompt evaluation and control measures. Materials and Methods: A total of 1754 patients with confirmed COVID-19 infection were admitted at MVJMC and RH, Bangalore, from July 1, 2020 to December 12, 2020. Various parameters such as demographical profile, symptomatology, risk factors, laboratory profile, and complications of 75 patients (4.27%) who succumbed were studied. Results: About 45.33% of the patients who died were older than 65 years. 77% of patients who died were males. About 61.33% had severe illness at the time of presentation. 84% of the patients who died had comorbid illnesses. Respiratory failure secondary to acute respiratory distress syndrome and bilateral pneumonia was the leading cause of mortality followed by sepsis/multiple organ dysfunction syndrome, myocarditis, coagulopathy, and acute cardiovascular event. The presence of lymphopenia elevated inflammatory markers, and comorbid conditions were identified as risk factors for the requirement of oxygen, mechanical ventilation, and death. Conclusion: Elderly patients (>65 years of age) and middle-age patients (45-65 years of age) comprised the highest and second-highest proportion of mortality respectively. The increasing proportion of deaths among the middle-aged patients and the narrowing gap of the same between these two groups are alarming. Old age, male gender, underlying chronic illnesses, and elevated inflammatory markers are some of the factors attributed to these trends. Hence, stringent preventive measures, early detection, and initiation of treatment pose a greater impact on reducing the burden of morbidity and mortality.